(779) Foreign Loans and Economic Development(Part 3): The I.B.R.D Approach القروض الأجنبية والتنمية الاقتصادية: الجزء الثالث: نهج البنك الدولي للتنمية - M. El-Imam, M. (INP, 2023)
This study explores international debt models, focusing on Alter’s model and its analysis of alternative debt constraints and their implications. It critiques the inadequacy of Alter’s conditions and introduces the Shahid Husain model to better understand the debt cycle. The research also examines the I.B.R.D. numerical model and the compound interest mechanism’s role in long-term debt formation. The findings highlight the dynamics of debt and its economic consequences. The appendices provide solutions to first-order difference equations and a numerical example of the I.B.R.D. model to illustrate potential debt accumulation scenarios.